Application of Atomic Force (AFM), Environmental Scanning Electron (ESEM) and Confocal Laser Scanning Microscopy (CLSM) in bitumen: A review of the ageing effect. (August 2021) - Pipintakos, Georgios; Hasheminejad, Navid; Lommaert, Caitlin; Bocharova, Anastassiya; Blom, Johan
Highlights: Typical bee-like structures with AFM change in size after short- and long-term laboratory ageing. The fibril network in ESEM is getting denser and coarser with ageing. CLSM fluorescent centres remain unaffected in terms of size by ageing or disappear upon oxidation. CLSM in reflectance mode is the most promising future microscopy for ageing in bitumen. A common preparation procedure for bituminous microscopic samples is proposed. Abstract: Undoubtedly bitumen's viscoelastic performance has received much attention in the literature. Especially, the oxidative ageing phenomenon of bitumen has been studied by several scholars from different physicochemical and mechanical perspectives due to its direct impact on asphalt performance. The microstructural patterns observed with ageing utilising different microscopic techniques have not remained unexplored, and an increasing interest has been expressed to understand the bitumen's architecture by coupling it with different theories. This review aims to provide a useful guide for the road engineer by collecting all the existing microstructural trends that have been reported upon ageing by utilising some of the most promising microscopic techniques. The study demonstrates the changes being observed for the size of the so-called bee structures via Atomic Force Microscopy (AFM). The apparent fibril microstructure captured with Environmental Scanning Electron Microscopy (ESEM) consistently reported in the literature to become denser and coarser with ageing. The existing findings of Confocal Laser Scanning Microscopy (CLSM) revealed the conflicting observations that exist for the fluorescent centres of bitumen upon oxidation, concerning their size and number. Finally, this paper provides a comparative analysis of the three techniques for bitumen applications and recommends a systematic sample preparation protocol to move towards more consistent observations between the different research groups.